The protective effect of oxytocin on ischemia/reperfusion injury in rat urinary bladder - ERCAN, FERİHA (ELSEVIER SCIENCE INC, 2013)
Oxytocin (OXY), a well-known nonapeptide, plays a crucial role in reproduction, and has effects on modulating the immune and inflammatory processes in living organisms as well. Recently it is also known as an antioxidant in several organs. The present study aims to demonstrate the protective effect of OXY against ischemia/reperfusion (UR) injury in urinary bladder tissue. Abdominal aorta of rats, were clamped to perform urinary bladder ischemia. OXY (0.5 mu g/kg) was injected intraperitoneally before ischemia in I/R+OXY group, whereas the vehicle solution was injected to I/R group. At the end of reperfusion, tissue samples from urinary bladder were processed for histochemical, ultrastructural and biochemical analysis. Tissue sections were stained by toluidine blue for mast cell counting and hematoxylin-eosin for histopathology. In addition, malondialdehyde (MDA) and glutathione (GSH) levels were determined biochemically. The results demonstrated that there was an extreme damage at urothelium, dilatation of intercellular junctions, inflammatory cell infiltration in I/R group. I/R+OXY group demonstrated a reduction in the severity of urinary bladder damage. According to mast cell counting results, both granulated and degranulated mast cells were decreased in I/R+OXY group compared to I/R group. The mean MDA level was higher in I/R group compared to control and lower in I/R+OXY group compared to I/R group. GSH level reduced in I/R group compared to the control and increased in I/R+OXY group compared to I/R group. In conclusion, oxytocin, as confirmed by histological evaluation and biochemical assays has a potential protective effect in the urinary bladder tissue against ischemia/reperfusion injury. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Ischemia/reperfusion; Oxytocin; Urinary bladder; ISCHEMIA-REPERFUSION INJURY; SKELETAL-MUSCLE; FREE-RADICALS; LIPID-PEROXIDATION; NEUTROPHIL; STRESS; RABBIT; LIVER